A Modern Epidemic Expert Perspectives on Obesity and Diabetes - Baur, Professor Louise A; Twigg, Stephen M; Magnusson, Roger S (Sydney University Press, 2012)
Diabetes, obesity and their related diseases make up one of the greatest challenges to human health in the 21st century. In A Modern Epidemic: Expert Perspectives on Obesity and Diabetes, a diverse group of researchers and clinicians from the University of Sydney has joined forces to discuss how to tackle these major health challenges. Obesity and diabetes are not just problems for the individual. They pose risks to the environmental, psychological and economic stability of the entire world. The solutions, therefore, need to be equally wide-ranging and accessible to all. Acknowledging this, the authors write in an engaging style about the causes and consequences of obesity and diabetes, as well as prevention and treatment: how to identify and mitigate the risk factors, deliver targeted and effective healthcare, and formulate global strategies to ultimately turn the tide on the 21st century's most devastating diseases.